Exploiting the role of O6-methylguanine-DNA-methyltransferase (MGMT) in gastrointestinal cancers - Wu, Ziming; Dai, Jie; Li, Jie; Zhang, Zhengyu; Shen, Xbing (Naunyn-Schmiedeberg's archives of pharmacology, 2025)
Gastrointestinal (GI) cancer is a prevalent disease and is recognized as the primary cause of cancer-related mortality globally. Therefore, there is an urgent need for novel diagnostic and treatment approaches for GC. The methylation of the O(6)-methylguanine DNA methyltransferase (MGMT) gene promoter is a significant factor in the development of colorectal cancer (CRC), namely in roughly 30–40% of cases where the cancer has spread. MGMT plays a role in the repair of DNA damage caused by methylating drugs like temozolomide (TMZ) and chloroethylating compounds like carmustine. As a result, it contributes to the resistance of chemotherapy when these agents are utilized. Although MGMT’s role in the development of CRC is well established, its prognostic significance remains a subject of debate. Only a limited number of research have been conducted to examine the prognostic significance of MGMT methylation, yielding varying outcomes. This review explores the structural functions and repair processes of MGMT, focusing on the putative structural and functional significance of the N-terminal domain of MGMT. It also investigates the advancement of cancer treatment techniques that specifically target MGMT.